2010
DOI: 10.1021/jm901561u
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Biophysical Properties of the Histone Deacetylase Inhibitor Suberoylanilide Hydroxamic Acid Are Affected by the Presence of Short Alkyl Groups on the Phenyl Ring

Abstract: Inhibition of histone deacetylases (HDACs) leads to growth arrest, differentiation, or apoptosis of tumor cell lines, suggesting HDACs as promising targets for cancer therapy. At present, only one HDAC inhibitor (HDACi) is used in therapy: suberoylanilide hydroxamic acid (SAHA). Here, we describe the synthesis and biological evaluation of a new series of compounds derived from SAHA by substituting short alkyl chains at various positions of the phenyl ring. Such modifications induced variable effects ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 41 publications
(79 reference statements)
0
20
0
Order By: Relevance
“…The positive effect of a meta-methyl had already been observed for hydroxamate-based inhibitors on total HDAC activity in Caco-2 colon cancer cells, meanwhile para-methyl analogues demonstrated slightly reduced inhibitory activity. 33 Ring contraction to γ-lactam (81, 128) afforded compounds with HDAC inhibitory potency comparable to those with larger δ-lactams, with similar SARs. Indeed, the presence of an (R)-ω-amide stereocenter significantly lowered the potency (145), even if to a lower extent than in the δ-lactam series.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The positive effect of a meta-methyl had already been observed for hydroxamate-based inhibitors on total HDAC activity in Caco-2 colon cancer cells, meanwhile para-methyl analogues demonstrated slightly reduced inhibitory activity. 33 Ring contraction to γ-lactam (81, 128) afforded compounds with HDAC inhibitory potency comparable to those with larger δ-lactams, with similar SARs. Indeed, the presence of an (R)-ω-amide stereocenter significantly lowered the potency (145), even if to a lower extent than in the δ-lactam series.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the intervening two decades, the list of HDAC inhibitors has expanded to include hydroxamic acids, short-chain fatty acids, boronic acids, α-keto acids, cyclic tetrapeptides, benzamides, ketones, isothiocyanates, organosulfur compounds, selenium-based compounds and their metabolites, and other miscellaneous agents (Minucci and Pelicci, 2006; Delage and Dashwood, 2009a; Lane and Chabner, 2009; Nian et al, 2009a,b; Suzuki et al, 2009; Desai et al, 2010; Noureen et al, 2010). Based on the features of the active site pocket in the presence and absence of bound ligands (Finnin et al, 1999; Vannini et al, 2004, 2007; Somoza et al, 2004; Bottomley et al, 2008; Dowling et al, 2008; Schuetz et al, 2008; Ficner, 2009), and computational modeling in silico (Vannini et al, 2007; Nian et al, 2008, 2009b; Ortore et al, 2009; Suzuki et al, 2009; Wang, 2009; Oger et al, 2010), numerous HDAC inhibitor candidates have been identified. These compounds typically have a functional group that interacts with the zinc atom in the enzyme pocket, a spacer “arm” that fits into the channel near the active site, and in many (but not all cases) a cap group that associates with residues near the surface.…”
Section: Hdac Inhibitors and Cancer Therapeutics—role Of Metabolismmentioning
confidence: 99%
“…The cap group in HDAC inhibitors lies close to the surface and can dictate specificity toward individual HDACs (Vannini et al, 2007; Nian et al, 2008, 2009b; Ortore et al, 2009; Suzuki et al, 2009; Wang, 2009; Oger et al, 2010). Interestingly, benzyl isothiocyanate (BITC) was reported to inhibit HDAC activity in human pancreatic carcinoma cells, and this was rescued by overexpression of HDAC1 or HDAC3 (Batra et al, 2010).…”
Section: Dietary Hdac Inhibitors—role Of Metabolismmentioning
confidence: 99%
“…Both the capping and the metal binding groups have been modified extensively in HDAC inhibitor design. 3540 In contrast, few studies report modification of the linker region. 4144 To study the effect of substitution on the linker region, SAHA analogs substituted at carbon 2 (C2), 3 (C3), or 6 (C6) of the linker region were synthesized and screened (Figure 1).…”
mentioning
confidence: 99%